Brown Adipose Tissue undergoes pathological perturbations and shapes C2C12 myoblast homeostasis in the SOD1-G93A mouse model of Amyotrophic Lateral Sclerosis - Marco Rosina; Silvia Scaricamazza; Flaminia Riggio; Gianmarco Fenili; Flavia Giannessi; Alessandro Matteocci; Valentina Nesci; Illari Salvatori; Daniela F. Angelini; Katia Aquilano; Valerio Chiurchiù; Daniele Lettieri Barbato; et al. (Heliyon)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by the selective loss of motor neurons. The contribution of peripheral organs remains incompletely understood. We focused our attention on brown adipose tissue (BAT) and its secreted extracellular vesicles (EVs) given their role in regulating systemic energy balance. In this study, we employed a multi-omics approach, including RNA sequencing (GEO identifier GSE273052) and proteomics (ProteomeXchange identifier PXD054147), to investigate the alterations in BAT and its EVs in the SOD1-G93A mouse model of ALS. Our results revealed consistent changes in the proteomic and transcriptomic profiles of BAT from SOD1-G93A mice, highlighting alterations such as mitochondrial dysfunction and impaired differentiation capacity. Specifically, primary brown adipocytes (PBAs) from SOD1-G93A mice exhibited differentiation impairment, respiratory defects, and alterations in mitochondrial dynamics. Furthermore, the BAT-derived EVs from SOD1-G93A mice displayed distinct changes in size distribution and cargo content. In parallel, such EVs negatively impacted the differentiation and homeostasis of C2C12 murine myoblasts, as well as induced atrophy in C2C12-derived myotubes. These findings suggest that BAT undergoes pathological perturbations in ALS mouse model and could impact on skeletal muscle homeostasis through the secretion of dysfunctional EVs.